Internalization of nanopolymeric tracers does not alter characteristics of placental cells. Issue 6 (14th March 2016) - Bigini, Paolo; Zanier, Elisa R.; Saragozza, Silvia; Maciotta, Simona; Romele, Pietro; Bonassi Signoroni, Patrizia; Silini, Antonietta; Pischiutta, Francesca; Sammali, Eliana; Balducci, Claudia; Violatto, Martina B.; Talamini, Laura; et al.
Abstract: In the cell therapy scenario, efficient tracing of transplanted cells is essential for investigating cell migration and interactions with host tissues. This is fundamental to provide mechanistic insights which altogether allow for the understanding of the translational potential of placental cell therapy in the clinical setting. Mesenchymal stem/stromal cells (MSC) from human placenta are increasingly being investigated for their potential in treating patients with a variety of diseases. In this study, we investigated the feasibility of using poly (methyl methacrylate) nanoparticles (PMMA‐NPs) to trace placental MSC, namely those from the amniotic membrane (hAMSC) and early chorionic villi (hCV‐MSC). We report that PMMP‐NPs are efficiently internalized and retained in both populations, and do not alter cell morphofunctional parameters. We observed that PMMP‐NP incorporation does not alter in vitro immune modulatory capability of placental MSC, a characteristic central to their reparative/therapeutic effects in vitro . We also show that in vitro, PMMP‐NP uptake is not affected by hypoxia. Interestingly, after in vivo brain ischaemia and reperfusion injury achieved by transient middle cerebral artery occlusion (tMCAo) in mice, iv hAMSC treatment resulted in significant improvement in cognitive function compared to PBS‐treated tMCAo mice. Our study provides evidence that tracing placental MSC with PMMP‐NPs does not alter their in vitro and in vivo functions. These observations are grounds for the use of PMMP‐NPs as tools to investigate the therapeutic mechanisms of hAMSC and hCV‐MSC in preclinical models of inflammatory‐driven diseases.